The State Of Financial Inclusion For Agriculture In Indonesia - Supartoyo, Yesi Hendriani (Jurnal Ekonomi Pertanian dan Agribisnis, 2023)
Financial inclusion is an important component in the process of social and economic inclusion, in order to boost economic growth, create financial system stability, support poverty alleviation, and reduce the gaps among people and regions. Based on the report of The Global Financial Inclusion Index (Findex) 2017, Indonesia as a developing economics received mainly in cash for the agricultural payments, than into an account. In the other hand, based on report of Financial Inclusion Insights Indonesia 2020, relate to account ownership by livelihood, account ownership is lowest in the agriculture sector and highest among professional and government workers. Digitizing payments for workers in the agricultural and informal sectors is an important means of expanding financial inclusion. Making agricultural payments through mobile phones could be especially helpful for unbanked farmers living in remote rural areas – many of whom have access to a phone. To improve financial inclusion for rural area and those who depend on agriculture for their livelihoods, the following policy measures should be pursued namely develop pilot that can help test the potential of these strategies. We also need to build transparent pricing platforms that provide smallholders with a full understanding. Strengthening financial inclusion as strategies initiatives that have proven to support the rural areas and agricultural sector. These initiatives would be important not only for facilitating the reallocation of resources to the rural, but also, and equally important, to promote rapid productivity growth within these sectors.